Visual impairment and risk of depression: A longitudinal follow-up study using a national sample cohort - Choi, Hyo Geun; Lee, Min Joung; Lee, Sang-Mok (Scientific reports, 2018)
The association of visual impairment and depression has been investigated in several studies based on a cross-sectional design, which cannot delineate temporal relationships. In the present study, we evaluated the influence of visual impairment on depression in all age groups using a longitudinal database of a national sample cohort from 2002 to 2013 provided by the Korean National Health Insurance Service. Of a total of 1,025,340 subjects, 5,846 participants who were registered as visually impaired persons without a previous diagnosis of depression were enrolled at a 1:4 ratio with 23,384 control participants matched for age, sex, income, and region of residence. The crude and adjusted (age, sex, income, region of residence, hypertension, diabetes, and dyslipidemia) hazard ratios (HRs) for the development of depression between the visually impaired and control groups were analyzed using a Cox proportional hazards model. Visual impairment increased the risk of depression after adjusting for age, sex, income, region of residence, hypertension, diabetes, and dyslipidemia (adjusted HR = 1.19, P = 0.002). The risk of depression increased significantly in both the non-blindness visual impairment (adjusted HR = 1.15, P = 0.036) and blindness subgroups (adjusted HR = 1.31, P = 0.016), with a higher HR in the blindness subgroup.